Born into Care: characterising newborn babies and infants in care proceedings in England and Wales - Bachar Alrouh; Karen Broadhurst; Lucy Griffiths; Rhodri Johnson; Linda Cusworth; Stuart Bedston; Ashley Akbari; Kerina Jones; David Ford (International Journal of Population Data Science, 2019)
Background/rationale Nations with advanced child protection systems place considerable emphasis on the developmental salience of infancy. However, this emphasis is not matched by any differentiated analysis of the timing of family court intervention in the lives of infants or the final legal order outcomes of these cases. This presentation shares findings from the first ever population profiling study of infants subject to care proceedings within the family justice system in England and Wales.